Variation in type of adjuvant chemotherapy received among patients with stage I breast cancer: A multi‐institutional study. Issue 12 (10th March 2015) - Vaz‐Luis, Ines; Hughes, Melissa E.; Cronin, Angel M.; Rugo, Hope S.; Edge, Stephen B.; Moy, Beverly; Theriault, Richard L.; Hassett, Michael J.; Winer, Eric P.; Lin, Nancy U.
<x xml:space="preserve">Abstract</x> BACKGROUND Among patients with stage I breast cancer, there is significant uncertainty concerning the optimal threshold at which to consider chemotherapy, and when considered, there is controversy regarding whether to consider non‐intensive versus intensive regimens. The authors examined the types and costs of adjuvant chemotherapy received among patients with stage I breast cancer. METHODS The current study was a prospective cohort study including patients with stage I breast cancer who were treated at a National Comprehensive Cancer Network center from 2000 through 2009. Stage was defined according to the version of the American Joint Committee on Cancer Staging Manual applicable at the time of diagnosis. Stratifying by human epidermal growth factor receptor 2 (HER2), the authors examined the percentage of patients receiving intensive versus non‐intensive chemotherapy regimens and the factors associated with type of chemotherapy administered using multivariable logistic regression. Costs of the most common regimens were estimated. RESULTS Of 8907 patients, 33% received adjuvant chemotherapy. Among those individuals, there was an increase in the use of intensive chemotherapy within the last decade, from 31% in 2000 through 2005 to 63% in 2008 through 2009 (including an increase in the use of the combination of docetaxel, carboplatin, and trastuzumab) among patients with HER2‐positive disease and from 15% in 2000 through 2005 to 41% in 2008 through 2009 among patients with HER2‐negative disease (32% of patients with hormone receptor‐positive and 59% of patients with triple‐negative disease). Among patients treated with non‐intensive regimens, there was an increase in the use of the combination of docetaxel and cyclophosphamide noted, with a decrease in the use of the doxorubicin and cyclophosphamide combination. The choice of regimen varied significantly by institution. The major drivers of cost variation were the incorporation of biologics (eg, trastuzumab) and growth factors, with significant variation even within non‐intensive and intensive regimens. CONCLUSIONS Over time, there was an increase in use of intensive regimens among Stage I breast cancer, with striking institutional and cost variations. Cancer 2015;121:1937–1948. © 2015 American Cancer Society.